DIGITAL TEACHING MATERIALS ABOUT GOVERNMENTAL ACCOUNTING FOR 3RD GRADE FROM MAITREYAWIRA TANJUNGPINANG VOCATIONAL HIGH SCHOOL - Muhammad Taufik; Julianti Julianti (ConCEPt - Conference on Community Engagement Project, 2022)
The online learning and teaching process at Maitreyawira Tanjungpinang Vocational Highschool is ineffective due to the Covid-19 pandemic. The limitations of online learning are the lack of interaction and feedback between teacher and student also the lack of tools and evaluation of online learning. Therefore, the preparation of teaching material is intended to provide videos and presentation slides as the tool and exercise questions in the module as the evaluation. The implementation method applied is observation through interview with school supervisor regarding the subject that is material and needs to be supported, namely Governmental Accounting for 3rd grade. The subject consists of eight chapters organized into three main parts, namely accounting transactions in the Working Unit and Village, financial reports in Village, and computerization accounting in Village with Siskeudes 2.0. The output is teaching materials in the form of learning modules containing materials and exercise questions, presentation slides, and videos. This activity provides academic literacy that is referred by student and teacher also distributes knowledge in difficult condition due to the Covid-19 pandemic.